2014
DOI: 10.1037/spq0000074
|View full text |Cite
|
Sign up to set email alerts
|

Well-being, school climate, and the social identity process: A latent growth model study of bullying perpetration and peer victimization.

Abstract: The present study concerns longitudinal research on bullying perpetration and peer victimization. A focus is on school factors of school climate (academic support, group support) and school identification (connectedness or belonging), which are conceptualized as related but distinct constructs. Analysis of change on these factors as well as individual well-being across time contributes to understanding bullying behavior. Latent growth modeling was employed to examine the predictors of anxiety, depression, 2 sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
81
2
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(103 citation statements)
references
References 58 publications
12
81
2
8
Order By: Relevance
“…This finding contradicts some of the existing literature (e.g., Bellmore et al, 2004;Turner et al, 2014) reporting that classroom makeup had an impact on bullying perpetration behaviors of the students. As this is one of the earliest studies investigating the impact of school setting regarding traditional bullying and cyberbullying in Australia, reasons for this contradiction can only be surmised.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…This finding contradicts some of the existing literature (e.g., Bellmore et al, 2004;Turner et al, 2014) reporting that classroom makeup had an impact on bullying perpetration behaviors of the students. As this is one of the earliest studies investigating the impact of school setting regarding traditional bullying and cyberbullying in Australia, reasons for this contradiction can only be surmised.…”
Section: Discussioncontrasting
confidence: 81%
“…However, we know that religious identity has been noted as one of the reasons for bullying perpetration (Collins, McAleavy, & Adamson, 2004;Puhl, Peterson, & Luedicke, 2013). Additionally, school climate (Klein, Cornell, & Konold, 2012), social identity with the school (Turner, Reynolds, Lee, Subasic, & Bromhead, 2014), classroom norms (Pozzoli, Gini, & Vieno, 2012) and classroom makeup (Bellmore, Witkow, Graham, & Juvonen, 2004) all have an important influence on bullying perpetration. We therefore, anticipate that a school context which is shaped by religious values can also have an impact on bullying perpetration of school children.…”
Section: Religious Makeup Of the School Settingmentioning
confidence: 96%
“…For instance, people with depression who engage in recreational social groups, or group psychotherapy, only experience improvement in their symptoms over time to the extent that they identify with the group in question (Cruwys, Haslam, Dingle, et al 2014a). The benefits of social identification for health have been demonstrated for a wide array of populations and specific conditions, including in pilgrims (Tewari et al 2012), school children (Turner et al 2014), people with multiple sclerosis (Wakefield et al 2013), or people who have experienced a traumatic event ).…”
mentioning
confidence: 99%
“…Another study found that the relationship between adolescent social support and behavioral problems were moderated by the perception of the school climate, and when changes over the course of a number of school years were negative, the behavioral problems increased (9). On the other hand, Australian high school students that perceived that there was more academic support and who had a good feeling with respect to the school environment saw fewer reports of victimization and bullying (12).…”
Section: Discussionmentioning
confidence: 99%